2015
DOI: 10.4236/oalib.1101583
|View full text |Cite
|
Sign up to set email alerts
|

Gene Mutations Associated with Temporomandibular Joint Disorders: A Systematic Review

Abstract: Background The temporomandibular joint (TMJ) is a bilateral synovial joint between the mandible and the temporal bone of the skull. TMJ disorders (TMDs) are a set of complicated and poorly understood clinical conditions, in which TMDs are associated with a number of symptoms including pain and limited jaw movement. The increasing scientific evidence suggests that genetic factors play a significant role in the pathology of TMDs. However, the underlying mechanism of TMDs remains largely unknown. Objective The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…In our study finding showed that the prevalence of appropriate IYCF practice was much better than the study conducted in Bahir Dar city (7%), 26 Assayita (9.2%), 28 and Shashemene which was 32.1%. 27 As indicated in the results of our study, around 80.1% % of mothers received delivery services at health facility. This implies a potential to deliver child feeding recommendations through counseling of mothers.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In our study finding showed that the prevalence of appropriate IYCF practice was much better than the study conducted in Bahir Dar city (7%), 26 Assayita (9.2%), 28 and Shashemene which was 32.1%. 27 As indicated in the results of our study, around 80.1% % of mothers received delivery services at health facility. This implies a potential to deliver child feeding recommendations through counseling of mothers.…”
Section: Discussionsupporting
confidence: 50%
“…25 There are fewer studies from the Ethiopian scenario related to IYCF practices that have revealed the appropriateness of breast and complementary feeding practices. [26][27][28] but it was also advisable that time-to-time assessment to find out the improvement in the feeding practices of IYC and keeping in view this concept for study has been planned.…”
Section: Introductionmentioning
confidence: 99%
“…While epidemiological data from both population and clinical setting showed a clear preponderance of women in the reproductive age presenting with TMD signs and/or symptoms, results from the OPPERA investigation did not find a greater rate of TMD symptoms among women as compared to men; similarly, the incidence rate of clinically verified TMDs was only marginally greater in females. In addition to the OPPERA study, a systematic review has also reported a total of 112 candidate genes specifically and significantly related to TMDs, explaining why a sex difference in TMD susceptibility may be observed. Hence, TMD‐related sex‐specific differences remain an interesting and challenging issue.…”
Section: Discussionmentioning
confidence: 99%
“…RefWorks (Proquest) was utilized to store all the citations found through the search process. Titles and abstracts of papers found in the database search were screened using the Primary Excel Workbook, as described previously (Sangani et al, 2015). Data related to both screening and reviewing of the full text of articles not excluded were documented in the Primary Excel Workbook.…”
Section: Methodsmentioning
confidence: 99%